PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE THE POWER OF TWO DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 2 2X11 ENAM LINGKUNG KAB. PADANG PARIAMAM - Beti, Roza; ZA, Nilawasti; Zulfaneti, Zulfaneti (STKIP PGRI Sumbar, 2013)
The comprehension in mathematics concept for students is still low becomes a basic of this research. The purpose of this research is to know what is the comprehension of mathematic concept for active Â learning type The Power of Two Â with Handout better than for implementation of convensional learningâs students for grade IX SMPN 2 2x11Enam Lingkung in 2013/2014. The type of this research is experimental research by using random planning focused on subject. The populations are students in grade IX SMPN 2 2x11Enam Lingkung Â in 2013/2014, which consist of five classes. Moreover, sample of this research is taken by random, IX3 is for experimental class and IX2 is for control class. The instrument of this research is the comprehension of mathematics concept test. The techniques of data analysis is using t test for one group by software MINITAB is got P-value = 0,001 smaller thanÂ Â = 0.05, so this hyphothesis is accepted. In conclusion, the comprehension of mathematics concept for implemented convensional learningâs students.